PERBEDAAN JUMLAH KOLONI STAPHYLOCOCCUS AUREUS PADA BEBERAPA KONSENTRASI PERASAN BUAH BELIMBING WULUH SECARA IN VITRO - igede sudarmanto (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2017)
Abstract : Plants bilimbi (Averrhoa bilimbi Linn) has been utilized by the public as a traditional medicinal plants to cure various diseases. The content of natural chemicals from bilimbi fruits are known to have an antibacterial effect, namely, flavonoids and phenols. Methicillin Resistant Staphylococcus aureus (MRSA) is a gram-positive bacteria resistant to antibiotics semisintesis. This research aims to identify the differences in the number of colonies of Staphylococcus aureus bacteria at some concentrations of bilimbi fruit filtrate in vitro. The design of the research is a post test only control group design. Measurement of the activity of bacteria using a colony counter with dilution method. The average number of colonies of Staphylococcus aureus bacteria that grow at a concentration of bilimbi fruit filtrate 10% as much as 59.33 x 108 CFU / ml; at a concentration of 20% as much as 1.33 x 108 CFU / ml; at a concentration of 30%, 40% and 50% contained no bacterial colonies growing. At a concentration of 10 % is able to inhibit the growth of Staphylococcus aureus bacteria, while at a concentration of 30 % has been able to kill the bacteria Staphylococcus aureus. There is a difference in the number of bacterial colonies of Staphylococcus aureus in some bilimbi fruit filtrate concentration (Averrhoa bilimbi Linn) in vitro (p = 0.000